HIV-Associated CD8 Encephalitis: A UK Case Series and Review of Histopathologically Confirmed Cases - Lucas, Sebastian B.; Wong, Kum T.; Nightingale, Sam; Miller, Robert F. (Frontiers in Neurology, 2021)
HIV-associated CD8-encephalitis (HIV-CD8E) is a severe inflammatory disorder dominated by infiltration of the brain by CD8+ve T-lymphocytes. It occurs in people with HIV, typically when the virus is apparently well controlled by antiretroviral treatment (ART). HIV-CD8E presents with symptoms and signs related to marked cerebral inflammation and swelling, and can lead to coma and death unless treated promptly with corticosteroids. Risk events such as intercurrent infection, antiretroviral therapy interruption, immune reconstitution inflammatory syndrome (IRIS) after starting ART, and concomitant associations such as cerebrospinal fluid (CSF) HIV viral escape have been identified, but the pathogenesis of the disorder is not known. We present the largest case series of HIV-CD8E to date (n=22), representing histopathologically confirmed cases in the UK. We also summarise the global literature representing all previously published cases with histopathological confirmation (n=30). Together these series, totalling 52 patients, provide new insights. CSF HIV viral escape was a frequent finding in HIV-CD8E occurring in 73% of those with CSF available and tested; ART interruption and IRIS were important, both occurring in 27%. Black ethnicity appeared to be a key risk factor; all but one UK cases were African, as were the majority of the previously published cases in which ethnicity was stated. We discuss potential pathogenic mechanisms, but there is no unifying explanation over all the HIV-CD8E scenarios.